2015
DOI: 10.1155/2015/684836
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Hardness of Quenched Medium Steel Using an Ultrasonic Nondestructive Method

Abstract: Developing new materials or improving their heat treatment techniques is key to industrial upgrades for increasing fastener product quality. Nowadays, high tensile strength bolts are heat-treated to achieve desired mechanical properties such as hardness, strength, toughness, and resistance to fatigue and wear. Ultrasound detection is one widely used nondestructive inspection technique. Based on the characteristics of wave transmission, the refraction, diffraction, and scattering of ultrasound wave velocity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Researchers have investigated the effect of hardness on ultrasonic wave velocity [21]. The authors demonstrated that the transmission, refraction, diffraction, and scattering characteristics of ultrasonic waves in the material depend on grain boundary features.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the effect of hardness on ultrasonic wave velocity [21]. The authors demonstrated that the transmission, refraction, diffraction, and scattering characteristics of ultrasonic waves in the material depend on grain boundary features.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasonic testing of adhesive joints has covered many areas, including the properties of the joints themselves and the materials being joined [6][7][8]. The effects of surface roughness for bonding and hardness on ultrasonic measurements have also been studied [9,10]. A literature analysis showed that the attenuation of an ultrasonic wave, estimated by the decrease in the gain of successive reflection pulses of this wave, imaged on the screen of an industrial or laboratory defectoscope, is sensitive to the surface roughness at high frequencies of ultrasonic transducers.…”
Section: Introductionmentioning
confidence: 99%
“…The first class, according to matrix base such as composites of metallic matrices MMCs, composites of ceramics matrices CMC, and composites of polymers matrices PMC. MMCs are a mixture of metals matrices such as Aluminum (Al), Magnesium (Mg), Iron (Fe), Cobalt (Co) and Copper (Cu) supported by ceramics reinforcements (Pb, W, and Mo) [4]. However, metallic matrix composites are mixture of a ceramic's matrices and included segments of graphite and aramid fibers KEVLAR as dispersed phases [4].…”
Section: Introductionmentioning
confidence: 99%
“…MMCs are a mixture of metals matrices such as Aluminum (Al), Magnesium (Mg), Iron (Fe), Cobalt (Co) and Copper (Cu) supported by ceramics reinforcements (Pb, W, and Mo) [4]. However, metallic matrix composites are mixture of a ceramic's matrices and included segments of graphite and aramid fibers KEVLAR as dispersed phases [4]. However, polymers matrices PMCs are obtained from thermosetting or thermoplastic materials and put it in glass, carbon, steel, or Kevlar fibers as reinforced medium [5].…”
Section: Introductionmentioning
confidence: 99%